The Contribution of Rat Studies to Current Knowledge of Major Depressive Disorder: Results From Citation Analysis - Carvalho, Constança; Peste, Filipa; Marques, Tiago A.; Knight, Andrew; Vicente, Luís M. (Frontiers in Psychology, 2020)
Major Depressive disorder (MDD) is the most severe depression type and one of leading causes of morbidity worldwide. Clinical research is the most effective and informative research approach to understand the causes and possible courses of treatment for MDD. However, it is costly, time-consuming and presents ethical limitations which leads to the use of other research approaches mainly animal models. Animal models are widely used to understand MDD etiology, pathogenesis and treatment, but the efficacy of this research for patients has barely been systematically evaluated. Such evaluation is important given the resource consumption and ethical concerns incurred by animal use. We used the citation tracking facilities within Web of Science and Scopus to locate citations of original research papers on rats related to MDD published prior to 2013 identified in PubMed and Scopus by relevant search terms. Resulting citations were thematically coded in eight categories, and descriptive statistics were calculated. 178 publications describing relevant rat studies were identified. They were cited 8,712 times. More than half (4,633) of their citations were by other animal studies. 794 (less than 10%) were by human medical papers. Citation analysis indicates that rat model research has contributed very little to the contemporary understanding of MDD. This suggests a misuse of limited funding hence supporting a change in allocation of Research & Development funds targeting this disorder maximizing benefits for patients.